Multiplexed Method to Calibrate and Quantitate Fluorescence Signal for Allergen-Specific IgE - Monroe, Margo R. (2011)
[Image: see text] Using a microarray platform for allergy diagnosis allows for testing of specific IgE sensitivity to a multitude of allergens, while requiring only small volumes of serum. However, variation of probe immobilization on microarrays hinders the ability to make quantitative, assertive, and statistically relevant conclusions necessary in immunodiagnostics. To address this problem, we have developed a calibrated, inexpensive, multiplexed, and rapid protein microarray method that directly correlates surface probe density to captured labeled secondary antibody in clinical samples. We have identified three major technological advantages of our calibrated fluorescence enhancement (CaFE) technique: (i) a significant increase in fluorescence emission over a broad range of fluorophores on a layered substrate optimized specifically for fluorescence; (ii) a method to perform label-free quantification of the probes in each spot while maintaining fluorescence enhancement for a particular fluorophore; and (iii) a calibrated, quantitative technique that combines fluorescence and label-free modalities to accurately measure probe density and bound target for a variety of antibody–antigen pairs. In this paper, we establish the effectiveness of the CaFE method by presenting the strong linear dependence of the amount of bound protein to the resulting fluorescence signal of secondary antibody for IgG, β-lactoglobulin, and allergen-specific IgEs to Ara h 1 (peanut major allergen) and Phl p 1 (timothy grass major allergen) in human serum.